Implementasi Pendidikan Karakter Moderasi Beragama Pada Sekolah Berbasis Budaya (Studi Kasus SMPN 3 Karanganyar Kebumen) - Septiana Putri Rahayu; Fikria Najiatama (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to describe the implementation of character education in religious moderation at SMP N 3 Karanganyar and to identify the obstacles and supporting factors in its implementation. This research uses a qualitative approach. The subjects of the study are eighth-grade students of SMP N 3 Karanganyar. The method applied is a case study method. The data collected focus on the implementation of character education in religious moderation within a culturally-based school. The data were analyzed using qualitative analysis techniques, including data reduction, data presentation, and conclusion drawing. Based on the results of the study, it can be concluded that the implementation of religious moderation in culturally-based schools aims to preserve and maintain existing cultural values while fostering students’ awareness to fulfill their religious obligations according to their respective beliefs. Through this implementation, students are able to develop tolerance, build harmony, and cultivate attitudes of mutual respect and appreciation amid the diversity present in the school environment